Ginger, Galangal, and Turmeric Production in Florida - Paul Fisher; Rosanna Freyre; Celina Gómez; Brian Pearson; Tatiana Sanchez-Jones; Shawn Steed; Wanda Laughlin; Robert Hochmuth; Jeff Wasielewski; Deah Lieurance; Carrie Harmon; Mathews Paret; et al. (EDIS)
Ginger, galangal, and turmeric (Figure 1) are emerging crops for Florida production. All of these plants are in the Zingiberaceae family and share most aspects of their production. This bulletin describes production in containers or the field under Florida conditions to help guide growers interested in ginger, turmeric, and galangal production or expanding their market. All species have been evaluated by the UF/IFAS Assessment of Non-native Plants in Florida’s Natural Areas (UF/IFAS Assessment) using the Predictive Tool (an invasion risk assessment) and all present a low risk of invasion in Florida (https://assessment.ifas.ufl.edu).